The relationship between inflation and economic growth: Experiences of some inflation targeting countries - Ramazan Ekinci; Osman Tüzün; Fatih Ceylan (Financial Studies, 2020)
The relationship between price stability and economic growth has gained importance as a fundamental reason for the monetary policies based on the inflation targeting regime. Nevertheless, there is no theoretical evidence as to which inflation level is considered to be high or low for economic decision-making units. Therefore,empirical findings are required to determine which inflation level is a threshold for the economic growth. The aim of this study is to examine the relationship between price stability and economic growth of the selected countries applying inflation targeting. We use threshold dynamic panel data model in order to make a comparison between inflation targeting countries. According to the findings of the study,the threshold value is 4,182%in inflation targeting countries. Below the threshold, the inflation-growth relationship is insignificant, and above the threshold, inflation affects economic growth negatively. This result shows that the inflation-economic growth relationship is nonlinear.
Keywords: E31; E52; 330; Monetary Policy; Emerging Countries; Threshold Dynamic Panel Data Analysis